AVOID: Adaptation and vulnerability of Nothofagus forests to drought-induced risks and disasters in Central and Southern Chile - (:unkn) unknown (My University, 2025)
This proposal is building on top of previous collaboration between the Chilean-German lead researchers, Drs. Aravena and Griessinger. This collaboration has included joint fieldwork activities in southernmost South America, dendroclimatic analysis, participation in workshops, among others. The Chilean team has also a long term collaborative work through national and international networks (IAI, Fondecyt, Pages). To develop this project will help to advance the dendroclimatic and eco-physiological studies in southern Andes incorporating new approaches that permit understand the response of native species to the strong climatic trends associated with climate change in this region. Isotopic analysis on tree rings is a novel methodological approach in southern South America with promising perspectives to advance the study of the response of species to climate change. The project will also help to the human resources formation with the participation of graduate students in interchange programs and with the reinforcing of the Chilean and German research groups with young researchers through post doc positions. The planned activities of this project include the development of one intensive program of fieldwork along a wide latitudinal transect in southern Andes, the organization of international workshops, shared data base analysis.